A Factor Model Analysis of the Australian Economy and the Effects of Inflation Targeting. Issue 314 (19th April 2020) - Hartigan, Luke; Morley, James
Abstract : Based on a dynamic factor model for a data set with more than 100 variables, we find that macroeconomic fluctuations in Australia can be largely captured by just two common factors. However, the factor structure changed soon after the introduction of inflation targeting in the 1990s, resulting in a large reduction in cross‐sectional variation related to these common factors. Estimates from a block‐exogenous factor‐augmented vector autoregressive model suggest that the transmission and responsiveness of monetary policy also changed, with policy both more effective and responsive to the potential inflationary impacts of shocks following the introduction of inflation targeting.